2021
DOI: 10.21203/rs.3.rs-618975/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Therapeutic and Prognostic Value of Chemokine Receptors (CXCRs) in Skin Cutaneous Melanoma (SKCM) Progression

Abstract: Introduction:Skin cutaneous melanoma (SKCM) is an aggressive cancer and associates with CXC chemokine receptors (CXCRs). CXCRs is a group of membrane protein involved in tumor initiation, progression, and outcome. However, the therapeutic and prognostic value of CXCRs in SKCM remained elusive. Methods: we used multiple, publicly available datasets for the analysis of CXCRs in SKCM. These datasets included GEPIA, UALCAN, TISIDB, DAVID 6.8, Metascape, GSCALite, and TIMER. Results: CXCR3 and CXCR4 were elevated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Malignant melanoma has an incidence of 15–25 per 100,000 individuals, which is increasing faster than any other cancers [ 28 ]. Metastatic malignant melanoma has a poor prognosis, with a 15–20% five-year survival rate [ 99 ]. Chemotherapy and radiation therapy are not considered to be good options for the treatment of metastatic melanoma because of treatment resistance [ 100 ].…”
Section: Cxcr4 In Solid Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant melanoma has an incidence of 15–25 per 100,000 individuals, which is increasing faster than any other cancers [ 28 ]. Metastatic malignant melanoma has a poor prognosis, with a 15–20% five-year survival rate [ 99 ]. Chemotherapy and radiation therapy are not considered to be good options for the treatment of metastatic melanoma because of treatment resistance [ 100 ].…”
Section: Cxcr4 In Solid Malignanciesmentioning
confidence: 99%
“…CXCR4 enhances the proliferation and survival of melanoma cells by increasing the number of tumour blood vessels. In vivo CXCR4 overexpression in melanoma has been reported [ 101 ] and has been found to be higher in metastasis than primary tumours, and, in addition, it is associated with a higher tumour stage [ 99 ]. In a meta-analysis of 13 studies investigating the CXCR4 expression in the tumour samples of 656 patients with malignant melanoma, it was found that the high expression of CXCR4 is associated with ulceration, increased tumour thickness and lymph node metastasis [ 102 ].…”
Section: Cxcr4 In Solid Malignanciesmentioning
confidence: 99%